Austria : Staff Report for the 2000 Article IV Consultation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2000)
The Austrian economy has been growing at an annual rate in excess of 3percent since mid-1999. Experience with deregulation in the telecommunications and electricity sectors is encouraged. With strong economic growth and expansionary monetary conditions from an Austrian perspective, Executive Directors judged that cyclical reasons would support a front-loaded approach to fiscal consolidation. Strong external demand and continued economic liberalization should contribute to sustaining economic expansion at a rate of close to 3percent per year in 2001-02.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet